Lateral Calcaneal Artery Perforator/Propeller Flap in the Reconstruction of Posterior Heel Soft Tissue Defects - T.M Balakrishnan; Liza J.; Abinaya Karthikeyan; Srividhya Madhurbootheswaran; M. Sugumar; M. Sridharan (Indian Journal of Plastic Surgery)
Introduction Posterior heel soft tissue defects with/without tendoachilles injury are difficult to reconstruct because of bony prominence, limited expendable local soft tissues, and significant donor site morbidity. In this study, we evaluate the lateral calcaneal artery (LCA) perforator/propeller flap for posterior heel soft tissue defect reconstruction.